Two Amino Acid Substitutions Improve the Pharmacological Profile of the Snake Venom Peptide Mambalgin - Dmitry I. Osmakov; Timur A. Khasanov; Ekaterina E. Maleeva; Vladimir M. Pavlov; Victor A. Palikov; Olga A. Belozerova; Sergey G. Koshelev; Yuliya V. Korolkova; Igor A. Dyachenko; Sergey A. Kozlov; Yaroslav A. Andreev (Toxins, 2025)
Mambalgins are peptide inhibitors of acid-sensing ion channels type 1 (ASIC1) with potent analgesic effects in models of inflammatory and neuropathic pain. To optimize recombinant peptide production and enhance pharmacological properties, we developed a mutant analog of mambalgin-1 (Mamb) through molecular modeling and site-directed mutagenesis. The resulting peptide, Mamb-AL, features methionine-to-alanine and methionine-to-leucine substitutions, allowing for a more efficient recombinant production protocol in E. coli. Electrophysiological experiments demonstrated that Mamb-AL exhibits three-fold and five-fold greater inhibition of homomeric ASIC1a and ASIC1b channels, respectively, and a two-fold increase in inhibition of heteromeric ASIC1a/3 channels compared with Mamb. In a mouse model of acetic acid-induced writhing pain, Mamb-AL showed a trend toward stronger analgesic efficacy than the wild-type peptide. These improvements in both production efficiency and pharmacological properties make Mamb-AL a valuable tool for studying ASIC channels and a promising candidate for analgesic drug development.